Effect of Seasonal Temperature on Oxygen Consumption in Relation to Body Size of a Fresh-Water Fish, the Flying Barb, Esomus dandricus (Ham.) - Bhattacharya, H.; Subba, B. R. (Our Nature, 2007)
Oxygen uptake in relation to body weight was measured in Esomus dandricus at two different seasonal temperatures, winter and summer. Oxygen uptake per unit time (mlO2/hr) increased from 0.5335 to 0.7839 with gradual increase in body weight from 0.5 to 1.5 g during winter season. During summer, it increased from 0.5539 to 1.4853 with an increase in body weight from 0.6 to 3.3 g. Oxygen uptake per unit time (mlO2/hr) increased by a power of 0.2594 while the oxygen uptake per unit weight (mlO2/g/hr) decreased by a power of -0.7409 at 16 ± 1 °C. Oxygen uptake rate per unit time (mlO2/hr) increased by a power of 0.5722 while the oxygen uptake per unit weight (mlO2/g/hr) decreased by a power of -0.4282 at 25 ± 1°C. As the slope of regression line relating to oxygen uptake (mlO2/hr) and body weight in Esomus dandricus is less than 1.0, it can be suggested that the oxygen uptake will decrease with increase in body weight of the fish. Keywords: Flying Barb, Oxygen consumption, Winter, Summer doi:10.3126/on.v4i1.503 Our Nature Vol. 4(1) 2006 pp53-60